Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan di Universitas Nahdlatul Ulama Surabaya (UNUSA) - Hansdoko, Rahasdita Reo; Panuju, Redi; Prasetyo, Iwan Joko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of job satisfaction on employee performance and the role of Nahdlatul Ulama (NU) values as a moderating variable at UNUSA. Using a quantitative approach and a questionnaire distributed to 84 permanent employees, the findings reveal that job satisfaction significantly enhances employee performance, particularly through aspects such as work environment, compensation, leadership, and career development. Although NU values do not statistically moderate the relationship, values such as tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i’tidal (justice) show a strong correlation with job satisfaction and contribute to creating a harmonious and fair work culture. The average scores of respondent perceptions indicate positive results, supporting the importance of integrating NU values into organizational practices. This study recommends strengthening managerial strategies related to job satisfaction and reinforcing the internalization of NU values.